The Role of Tafsīr Maqāṣidī in Contemporary Qur'anic Studies: An Analysis of Research at MIAT UIN Sunan Kalijaga - Chirzin, Muhammad; MZ, Ahmad Murtaza; Huzaifah, Huzaifah (Fakultas Ushuluddin, Adab dan Dakwah IAIN Kerinci, 2024)
The study of the Qur'an in Indonesia is currently undergoing significant transformations to maintain the relevance of its teachings in a modern context. The State Islamic University (UIN) Sunan Kalijaga, particularly the Master's Program in Qur'anic Studies and Interpretation (MIAT), has developed a new approach called tafsīr maqāṣidī, introduced by Abdul Mustaqim in 2019. This approach emphasizes understanding the objectives and principles of Sharia behind the Qur'anic text, allowing for interpretations that are more responsive to contemporary issues. This research aims to critically evaluate the application of tafsīr maqāṣidī in the theses of MIAT students at UIN Sunan Kalijaga, focusing on the depth, consistency, and quality of the interpretations, as well as identifying their strengths and weaknesses. The research question posed is: How does the application of tafsīr maqāṣidī enrich Qur'anic studies, and what challenges are faced in its implementation? The methodology used is a qualitative approach applying the reader-response theory, which asserts that the meaning of a text is formed through the interaction between the text and its readers. Analysis of various theses shows that tafsīr maqāṣidī enriches Qur'anic studies by linking the sacred text with contemporary issues such as the environment, governance, and social problems. However, limitations were found in the mastery of Arabic, ushul fiqh (principles of Islamic jurisprudence), classical Islamic texts (turāth), and engagement with contemporary studies, which affect the quality of interpretations. This research impacts a more comprehensive understanding of the application of tafsīr maqāṣidī and identifies areas that need improvement. Recommendations are provided to strengthen competencies in these areas so that tafsīr maqāṣidī can continue to develop and contribute significantly to Qur'anic studies in Indonesia. Studi Al-Qur'an di Indonesia kini mengalami transformasi signifikan untuk menjaga relevansi ajarannya dalam konteks modern. UIN Sunan Kalijaga, khususnya Program Magister Ilmu Al-Qur'an dan Tafsir (MIAT), telah mengembangkan pendekatan baru yaitu tafsīr maqāṣidī yang diperkenalkan oleh Abdul Mustaqim pada 2019. Pendekatan ini menekankan pemahaman tujuan dan prinsip syariah di balik teks Al-Qur'an, memungkinkan interpretasi yang lebih responsif terhadap isu-isu kontemporer. Penelitian ini bertujuan mengevaluasi kritis penerapan tafsīr maqāṣidī dalam tesis-tesis mahasiswa MIAT UIN Sunan Kalijaga, dengan fokus pada kedalaman, konsistensi, dan kualitas penafsiran, serta mengidentifikasi kekuatan dan kelemahannya. Metode yang digunakan adalah pendekatan kualitatif dengan menerapkan teori tanggapan pembaca (reader-response theory), yang menegaskan bahwa makna teks terbentuk melalui interaksi antara teks dan pembacanya. Analisis terhadap berbagai tesis menunjukkan bahwa tafsīr maqāṣidī memperkaya kajian Al-Qur'an dengan mengaitkan teks suci dengan isu-isu seperti lingkungan, tata kelola pemerintahan, dan masalah sosial. Namun, ditemukan keterbatasan dalam penguasaan bahasa Arab, ushul fiqh, kitab turāth, dan keterlibatan dengan kajian kontemporer, yang mempengaruhi kualitas penafsiran. Penelitian ini berdampak pada pemahaman lebih komprehensif tentang penerapan tafsīr maqāṣidī dan mengidentifikasi area yang perlu ditingkatkan. Rekomendasi diberikan untuk memperkuat kompetensi di bidang-bidang tersebut agar tafsīr maqāṣidī dapat terus berkembang dan berkontribusi signifikan dalam studi Al-Qur'an di Indonesia.